Taxonomic and Thematic Relatedness Ratings for 659 Word Pairs - Jon-Frederick Landrigan; Daniel Mirman (Journal of Open Psychology Data, 2016)
These data are comprised of taxonomic and thematic relatedness ratings for 300 target words paired with taxonomically related and/or thematically related words for a total of 659 word pairs. The pairs come from 4 prior studies and were normed through surveys provided online using Amazon’s Mechanical Turk. Pairs were rated in terms of both their taxonomic similarity and their thematic relationship. The data are provided as comma-separated (.csv) and R data (.rdata) files and can be used to create new studiesinvestigating taxonomic and thematic semantic processing.